Trends and Economic Assessment of Integration Processes at the Metal Market - Romanova, Olga Aleksandrovna; Makarov, Eduard Vyacheslavovich (Economy of Regions, 2015)
The article discussed the integration process from the perspective of three dimensions that characterize the corresponding increase in the number and appearance of new relationships; strength, character, and stability of emerging communications; dynamics and the appropriate form of the process. In the article, trends of development of integration processes in metallurgy are identified, identification of five stages of development in Russian metal trading are justified. We propose a step by step way to implement the integration process, developed a methodical approach to assessing the feasibility of economic integration processes steel producers and steel traders, including three consecutive stages of its implementing respectively, the principles of reflexive control, entropy approach, the traditional assessment of mergers and acquisitions. The algorithm for the practical realization of the author’s approach, which allows to identify the optimal trajectory of the integration process as a series of horizontal and vertical integration steps is developed.